Rhinoplasty with Concurrent Repair of Septal Perforation - Jones, Evan A.; Olson, Krista L. (Facial Plastic Surgery, 2023)
Concurrently performing septal perforation repair and rhinoplasty is challenging. Successful management of patients who require or desire these procedures performed simultaneously can be achieved with appropriate preoperative workup and optimization, thoughtful surgical planning, masterful execution, and diligent postoperative care. Consideration of perforation etiology and status of the perforation along with overall nasal health are the foundation upon which surgery may be planned. Preoperative evaluation to determine locations of obstruction, aesthetic goals, and feasibility of procedure is required. Rhinoplasty techniques and perforation closure techniques may share common maneuvers making concurrent surgery possible. Surgical techniques to achieve perforation closure often influence rhinoplasty considerations, and vice versa. Care must be taken to account and possibly even to capitalize on these influences. Perforation closure techniques that may be readily combined with rhinoplasty include interposition grafting and intranasal mucosal rotational advancement flaps, which may exert forces upon the nose with aesthetic or functional consequences. Rhinoplasty techniques targeting any third of the nose also can impact tension or available mucosa for perforation closure techniques. Combining these procedures can be very rewarding for the patient and provider but should be considered responsibly and thoughtfully.
Keywords: rhinoplasty and septal perforation; mucosal flaps; perforation repair; combined rhinoplasty